The world's most popular manga dragon ball : goku vs. piccolo - Toriyama, Akira (San Francisco : VIZ Media, 2021)
IAs the "Strongest Under the Heavens" martial arts tournament draws to a close, only Goku, Piccolo, and Shen--the disguised Kami-sama--remain! But even a god is no match for Piccolo's new powers, and soon Goku finds himself fighting...alone... in a battle which will decide not just who is strongest, but who or what will rule the world! The audience flees for their lives as the struggle shakes the heavens apart in the gripping conclusion of Akira Toriyama's Dragon Ball
VOL 16
Keywords: science-fiction